The Correlation between Intensity of Smartphone Usage with Social Media Addiction, Fear of Missing Out, and Need for Touch among Adolescents - Has, Eka Mishbahatul Mar’ah; Istianah, Nia; Qona’ah, Arina (International Journal of Psychosocial Rehabilitation, 2020)
Excess smartphone use among adolescents not only can cause physical health-related problems, but also psychological problems. The purpose of this study is to analyze the correlation between the usage intensity of smartphones with social media addiction, fear of missing out and need for touch which is experienced by adolescents. This was a descriptive-analytic study with a cross-sectional approach. The study enrolled 314 adolescents who were recorded as senior high school students in Surabaya, East Jawa, Indonesia, identified using a convenience sampling technique. The independent variable was the usage intensity of smartphones, while the dependent variables were social media addiction, the fear of missing out, and the need for touch. Data were collected using four different questionnaires, consisting of Smartphone Use Frequency (SUF), Bergen Social Media Addiction Scale (BSMAS), The Fear of Missing Out (FOMO) questionnaire, and The Need for Touch Scale (NFTs). Data were then analyzed by using Spearman Rank Correlation with the level of significance α=0.05. The study revealed that the usage intensity of smartphones is significantly correlated with social media addiction (p=0.000; r=0.318), fear of missing out (p=0.000; r=0.255), and the need for touch (p=0.000; r=0.196). It can be concluded that the more intensively adolescents use a smartphone, the more they are at risk of experiencing social media addiction, fear of missing out, and need for touch. Therefore, nurses should design a health promotion program for adolescents, so they can use smartphones wisely to prevent smartphone-related problems.